Contentious Ethical and Legal Aspects of Determination of Brain Death - Lewis, Ariane (Seminars in Neurology, 2018)
Although the concept of death by neurologic criteria is accepted throughout much of the world and death can legally be determined by neurologic criteria throughout the United States, the process is fraught with contentious ethical and legal controversies. I explore historic and contemporary ethical and legal disputes about determination of death by neurologic criteria including the need for consent from patients' surrogates prior to determination of death, the role of religion in determination of death, management of objections to determination of death by neurologic criteria, the approach to patients who are dead by neurologic criteria but are pregnant, and gamete retrieval after determination of death.
Keywords: brain death; ethics; medicolegal